Comparative sensitivity among early life stages of the South American toad to cypermethrin-based pesticide - Svartz, Gabriela Veronica (2015)
Cypermethrin is one of the most widely used pesticides due to its low mammalian and bird toxicity, but it is extremely toxic to aquatic organisms. The aim of the present study was to evaluate the toxicity of a commercial formulation of cypermethrin on the embryo?larval development of Rhinella arenarum. An ecological risk assessment based on the hazard quotient (HQ) approach was performed. The results showed that cypermethrin toxicity was stage-dependent and dramatically increased during the larval period. Thus, larvae were more sensitive than embryos, obtaining at the end of the experiment a 336-h median lethal concentration (LC50) of 0.65 μg cypermethrin/L. Cypermethrin exposure caused morphological abnormalities such as general underdevelopment, edema, gill malformations, and behavioral alterations as hyperkinesia and spasmodic contractions. The 168-h teratogenic index was 5, implying a high risk for embryos to be malformed in the absence of significant embryonic lethality. Based on the results of the toxicity effects and the  ecological risk assessed (HQ for chronic exposure>level of concern), this pesticide should be  considered as a direct (effects on survival) or indirect (severe sublethal effects) risk for  conservation purposes of this amphibian in agroecosystems.